Periodontitis: single-visit versus multiple-visit endodontics (LLC "Endo Press", 2020)
Single-visit or multiple-visit endodontic treatment of periodontitis is still controversial. Calcium hydroxide is the material of choice for intracanal dressing between appointments for absolute majority of endodontists. Nevertheless, there is no consensus in the literature for or against the use of calcium hydroxide for root canal temporary filling. In some clinical cases one-visit endodontics may be not only more effective but preferable option.